Proses-proses dalam organisasi yang mempengaruhi pembelajaran dalam Malaysia Airport Berhad, Cawangan Sarawak. - Hema, Hamidi (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study aims to look at how far organizational's processes influence the learning at Malaysia Airport Berhad (M. A. B. ), Sarawak Regional Office. The respondents consist of the subordinates from seven units at M. A. B. The processes are teamwork, decision making and latest technology application. 70 respondents are picked randomly out of the overall total of employees. 70 sets of questionnaires are used as the research instrument. Descriptive statistics design, that concludes Pearson Correlation is used as the data analysis method in order to find the relation between these processes and learning occured at M. A. B. The result shows the r value for teamwork and decision making are 0.639 and 0.569. Therefore these two processes are significantly correlated to learning. However, r value for latest technology application is 0.169. This value is less than 0.5. herefor, it is not significantly correlated to learning at M. A. B. Linear Regression Test is used to find the dominant process that influence learning at M. A. B. Through that test, it is found that teamwork is the dominant process in increasing the progress of learning among the subordinates.